Recent Developments in Textual Criticism - Van der Bergh, Ronald H. (2006)
This book contains a collection of essays read at a conference organized by the Netherlands School for Advanced Studies in Theology and Religion in January 2001. However, most of the essays have been thoroughly revised and two essays have been added.
Keywords: Rezension